UJI BANDING TEKANAN KEBOCORAN JALAN NAFAS ANTARA SUNGKUP LARING I-GEL DAN PIPA ENDOTRAKHEAL - , Diah Annisa Oktaviningsih ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background.The endotracheal tube has been the best methods in airway management, since itâs very effective in protecting the airway by preventing aspiration caused by the regurgitation of gastric acid. Today, there are many supraglottic airway tools that were used because of having little effect on the disturbance cardiovascular system since they were less invasive than the endotracheal tube. I-Gel was a new and inovative airway managementâs tool with elastic non air cuff that considered to be effective during spontaneus ventilation anaesthesi, or with positive pressure ventilation. One of the disadvantage of I-Gel compared to the ordinary endotracheal tube is ventilation disturbance if there were any leak, and the risk of regurgitation caused by gastric insufflation. By knowing the leak pressure from the I-Gel, the anaesthetist could give a much more effective ventilation when the given positive ventilation was not exceeding the airway pressure leak. Objective. Clinical trial of the airway leak pressure between the I-Gel and endotracheal tube. Methods. Randomized controlled trial. The subjects were patients the were underwent surgical procedure with a general anaesthesia using supraglottic airway management tools in the Central Operating Room Sardjito General Hospital. This they has been approved by the ethic committee and the patient had signed the informed consent. There were 106 patients entered by the inclusion and exclusion criteria, divided in to two groups, the A group received general anaesthesia using I-Gel laryngeal mask, and B received general anaesthesia using endotracheal tube. Airway leaks pressure was measured by closing the expiration valve, closing the ventilation bag, APL in the anaesthetic machine with 3l/mnt FGF of O2, the airway leakage pressure were reached at the pressure the manometer aneroid when no more increase. Result The airway leakage pressure using I gel were 25,81 Â± 8,093 where are no leakage using endotrakeal tube until airway pressure to 40 cmH2O. Conclusion There was a significant difference between leakage pressure in the IGel compared to the endotracheal tube.